DETERMINANTS OF CONSUMPTION PATTERNS OF HALAL SKINCARE PRODUCTS AMONG MUSLIM WOMEN IN JABODETABEK - Andi Azizah (Department Islamic Economics, 2025)
Goal: This study aims to examine the factors influencing halal lifestyle, religiosity, price, and social media on the consumption patterns of halal skincare among Muslim women in Jabodetabek. Methode: The type of research employed is descriptive quantitative, using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach to construct a model of halal skincare consumption patterns. A questionnaire was distributed through an online platform using purposive sampling technique, with the sample size determined using Slovin's formula, resulting in 100 Muslim female respondents residing in Jabodetabek. Fact/Finding: The findings of this study indicate that the variables of religiosity and social media have a positive and significant impact on the consumption patterns of halal skincare among Muslim women in Jabodetabek. In contrast, the variables of halal lifestyle and price do not have a positive and significant impact on the consumption patterns of halal skincare among Muslim women in Jabodetabek.